Synthesis of (Ca,Nd)TiO3 powders by complex polymerization, Rietveld refinement and optical properties - Marques, V. S.; Cavalcante, L. S.; Sczancoski, J. C.; Paris, E. C.; Teixeira, J. M. C.; Varela, José Arana [UNESP]; Vicente, Fábio Simões de [UNESP]; Joya, M. R.; Pizani, P. S.; Li, M. Siu; Santos, M. R. M. C.; Longo, Elson [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
Neodymium calcium titanate, (Ca0.99Nd0.01)TiO3 powders were synthesized by the complex polymerization method and heat treated at different temperatures for 2 h under air atmosphere. The structural evolution of these powders as a function of heat treatment temperature was analyzed by X-ray diffraction (XRD) and micro-Raman (MR) spectroscopy. The optical properties were investigated by Ultraviolet-visible (UV-vis) absorption spectroscopy and Photoluminescence (PL) measurements. XRD patterns, Rietveld refinement and MR spectra indicated that the powders heated treated at 750 degrees C for 2 h present an orthorhombic structure without secondary phases. UV-vis measurements suggested the presence of intermediary energy in disordered (Ca0.99Nd0.01)TiO3 powders. Broad and narrow bands were observed in the PL spectra of these powders when excited with 350 nm wavelength. The broad bands were associated to the structural defects and/or p-d electronic transitions while, the narrow bands were ascribed to f-f transitions arising from Nd3+ ions. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: (Ca0.99Nd0.01)TiO3; Rietveld refinement; f-f transitions; Photoluminescence